Divide and Conquer treemaps: Visualizing large trees with various shapes. (December 2015) - Liang, Jie; Vinh Nguyen, Quang; Simoff, Simeon; Lin Huang, Mao
Abstract: Most existing treemaps achieve the space utilization of a single geometrical area, mostly rectangle. Limiting visualization to rectangles could block the human capability on graph recognition, including orientation, shape and differentiation etc. To relax rectangular constraint, we propose a flexible enclosure approach with three algorithms. It partitions large hierarchical structures within a confined display area with different shapes for real-time applications. Our approach is based on the combination of Divide-and-Conquer method and the treemap paradigm. The partitioning algorithms generate three types of layouts with polygonal, angular and rectangular titling, which are flexible to be used separately or combined. We present technical details including the visualization results in the experiments and in the cases studies with real data sets. We evaluated the visualization based on graph drawing aesthetics and optimization criteria. Our usability study shows that (1) treemaps with layout variability support utilization of human capability in graph perception and (2) treemaps adopted in different shaped containers could have a positive impact on user satisfaction and awareness during visual data exploration. Highlights: A flexible visualization to relax rectangular constraint for large trees. The approach of combining Divide-and-Conquer method and the treemap׳s paradigm. The algorithms generate polygonal, angular and rectangular tessellation. Evaluation proves the efficiency based on optimization criteria and user studies.